1982
DOI: 10.1128/aac.22.4.693
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Stability of Newly Introduced β-Lactam Antibiotics to Renal Dipeptidase

Abstract: Renal dipeptidase purified from swine kidney hydrolyzed N -formimidoyl thienamycin, carpetimycins A and B, and Sch29482, but not azthreonam, penicillin G, or cephaloridine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

1985
1985
2000
2000

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 14 publications
(9 reference statements)
0
9
0
Order By: Relevance
“…Hydrolysis was assayed spectrophotometrically as described previously (2,8,13). One unit of the enzyme was defined as the amount of the enzyme which hydrolyzed 1 ,umol of a substrate per min at 35°C.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Hydrolysis was assayed spectrophotometrically as described previously (2,8,13). One unit of the enzyme was defined as the amount of the enzyme which hydrolyzed 1 ,umol of a substrate per min at 35°C.…”
mentioning
confidence: 99%
“…The kinetic parameters of the enzyme are shown in Purification of human dehydropeptidase by a previously described treatment (8) was unsuccessful, since enzyme activity was lost. Shibamoto et al (9) reported that PS-5 inactivating factor was fractionated by the differential cen-ANTIMICROB.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Renal dehydropeptidase 1 was purified from hog kidney cortex by the procedure described previously (8 …”
mentioning
confidence: 99%
“…Renal dehydropeptidase 1 was purified from hog kidney cortex by the procedure described previously (8). Hydrolysis of the compounds was assayed spectrophotometrically (1) by measuring the decrease in absorbance at the substrate-specific wavelength in a temperature-controlled spectrophotometer (8).…”
mentioning
confidence: 99%